Long‐read nanopore DNA sequencing can resolve complex intragenic duplication/deletion variants, providing information to enable preimplantation genetic diagnosis. (18th January 2022) - Watson, Christopher M.; Holliday, Deborah L.; Crinnion, Laura A.; Bonthron, David T.
Abstract: Background: The adoption of massively parallel short‐read DNA sequencing methods has greatly expanded the scope and availability of genetic testing for inherited diseases. Indeed, the power of these methods has encouraged the integration of whole genome sequencing, the most comprehensive single approach to genomic analysis, into clinical practice. Despite these advances, diagnostic techniques that incompletely resolve the precise molecular boundaries of pathogenic sequence variants continue to be routinely deployed. This can present a barrier for certain prenatal diagnostic approaches. For example, the pre‐referral workup for couples seeking preimplantation genetic diagnosis requires intragenic dosage variants to be characterised at nucleotide resolution. Objective: We sought to assess the use of long‐read nanopore sequencing to rapidly characterise an apparent heterozygous RB1 exon 23 deletion that was initially identified by multiplex ligation‐dependent probe amplification (MLPA), in a patient with bilateral retinoblastoma. Methods: Target enrichment was performed by long‐range polymerase chain reaction (PCR) amplification prior to Flongle sequencing on a MinION long‐read sequencer. Results: Characterisation of the deletion breakpoint included an unexpected 85‐bp insertion which duplicated RB1 exon 24 (and was undetected by MLPA). The long‐read sequence permitted design of a multiplex PCR assay, which confirmed that the mutation arose de novo. Conclusion: Our experience demonstrates the diagnostic utility of long‐read technology for the precise characterisation of structural variants, and highlights how this technology can be efficiently deployed to enable onward referral to reproductive medicine services. Key points: What's already known about this topic? Molecular diagnostic techniques that incompletely resolve pathogenic sequence variants can present a barrier for certain prenatal diagnostic approaches. What does this study add? This study demonstrates how nanopore‐based sequencing could be rapidly deployed for follow‐up analysis of previously identified, but incompletely‐defined structural variants, enabling onward referral to a national preimplantation genetic diagnosis service.